The Faktor-Faktor Yang Mempengaruhi Akuntabilitas Pengelolaan Keuangan Dana BTT Covid 19 Pemerintah Provinsi Sumatera Barat - Ike Roza Mardian; Yurniwati Yurniwati (Owner : Riset dan Jurnal Akuntansi, 2022)
Accountability is an obligation to be responsible for the implementation of activities and final results to the community as the holder of the obligation, in accordance with the provisions of the legislation. The people through the DPR/DPRD give authority to the government to manage economic resources, therefore the government has the obligation to convey responsibility, report, present and disclose all activities and activities that are the responsibility of management. This research is to examine the effect of the Government's Internal Control System, information technology and organizational commitment to the Accountability of Financial Management of the Covid 19 BTT Fund in the West Sumatra Provincial Government. The data processed is primary data obtained directly from respondents, namely financial and asset managers at the Regional Apparatus Organization (OPD) of the West Sumatra Provincial Government which manages the BTT Covid 19 budget for the 2020 and 2021 Fiscal Years. The results showed that the Government's Internal Control System had an effect on the Accountability of Financial Management of the BTT Covid 19 Fund with the highest indicator being the control environment dimension and the lowest indicator being the risk assessment dimension, while information technology and organizational commitment had no effect on Management Accountability. Finance of the BTT Covid 19 Fund.